Synthesis of Metal Organic Frameworks (MOFs) and Their Derived Materials for Energy Storage Applications - Sunil Dutt; Ashwani Kumar; Shivendra Singh (Clean Technologies, 2023)
The linkage between metal nodes and organic linkers has led to the development of new porous crystalline materials called metal–organic frameworks (MOFs). These have found significant potential applications in different areas such as gas storage and separation, chemical sensing, heterogeneous catalysis, biomedicine, proton conductivity, and others. Overall, MOFs are outstanding candidates for next-generation energy storage devices, and they have recently attracted the greater devotion of the scientific community worldwide. MOFs can be used to enhance the ability of a device to store energy due to their unique morphology, controllable structures, high surface area, and permanent porosity. MOFs are widely used in super capacitors (SCs), metal (Li, Na, and K) ion batteries, and lithium–sulfur batteries (LSBs) and act as a promising candidate to store energy in an environmentally friendly way. MOFs are also used as efficient materials with better recyclability, efficiency, and capacity retention. In this review, first we summarize the material design, chemical compositions, and physical structure of MOFs and afterward, we highlight the most recent development and understanding in this area, mainly focusing on various practical applications of MOFs in energy storage devices.